ANALISIS PENGARUH METODE SRI DAN KONVENSIONAL TERHADAP LUAS LAYANAN IRIGASI PADA BENDUNGAN MENINTING - MUH BAGUS BUDIANTO; HUMAIRO SAIDAH (GANEC SWARA, 2023)
The biggest water demand is in the agricultural sector. This great need is caused by the irrigation system with continuous inundation (conventional). One of the water-saving irrigation methods is the System of Rice Intensification (SRI) method. The SRI method of giving water is done intermittently. One of the obstacles to the application of the SRI method is a continuous water source. The dam is one of the water sources whose water availability is relatively easy to manage, making it suitable for irrigation applications using the SRI method. This study aims to analyze the provision of irrigation water for SRI and conventional systems at the Meninting Dam and its effect on the area of irrigation services. In this study, an analysis of water availability was carried out using awlr data, an analysis of irrigation water requirements using the conventional method and the SRI method. Reservoir simulation analysis is used to determine the area that can be irrigated, planting intensity and reservoir reliability. The results for the conventional method of irrigated area that can be served are 1,559 ha with a planting intensity of 300% and a reservoir reliability of 95.83%. At the same intensity and reliability as the conventional method, the SRI method can irrigate 1,980 ha of irrigation area, so using the SRI method can increase the service area by 421 ha or can increase the service area by 27%.